A randomized controlled trial of acute pancreatitis in Thanjavur medical college: an institutional experience - Jagatheesan, S.; John, Nikhil (International Surgery Journal, 2023)
Background: Acute pancreatitis is a prevalent gastrointestinal illness leading to hospitalizations in India, treated with rest, fluids, and analgesia. This study aimed to compare minimalistic and standard treatments for mild and moderate acute pancreatitis at Government Thanjavur Medical College. The outcome of patients with these conditions was assessed. Methods: Conducted from July 2020 to July 2022, the randomized controlled trial enrolled acute pancreatitis patients, classified as mild, moderate, or severe based on the Revised Atlanta criteria. All mild and moderate cases were included and randomly assigned to two groups. Group one received early oral diet, hydration, and analgesia, omitting somatostatin analogues and antibiotics. Group two underwent comprehensive management. The outcomes of 130 patients, including those during the COVID-19 peak, were analyzed. Results: No significant difference was found in the outcomes of patients with mild and moderate pancreatitis between the two treatments. All patients showed improvement during their hospital stay. Evaluation included hospital stay duration, sepsis development, and occurrence of local/systemic complications. Among them, three patients progressed to severe pancreatitis, with one fatality. Conclusions: For mild and moderate pancreatitis, a minimalistic approach yielded comparable outcomes to active management. However, severe pancreatitis should follow existing guidelines, emphasizing prompt management of complications and systemic organ support.